Leak-off and cleanup behavior of fracturing fluids in the presence of mobile hydrocarbons. - Gadiyar, Balkrishna Ramesh. (My University, 1997)
Leak-off characteristics in the presence of mobile gas or oil saturation are significantly different compared to those observed in the presence of 100% brine saturation. In the case of mobile gas saturation, the spurt loss appears to be driven by spontaneous imbibition, whereas the long-time leak-off is controlled by relative permeability effects. The wall building coefficients are at least an order of magnitude lower than those observed in 100% brine saturated core samples. The fluid loss additive used in this study appears to have little or no effect on leak-off. In the case of mobile oil saturation, both oil viscosity and relative permeability effects play a role in determining the leak-off response. The spurt loss is significantly lower than that observed in 100% brine saturated core samples. In this case also, the fluid loss additive has little or no effect on leak-off. The leak-off characteristics exhibit noticeable sensitivity to the formation permeability.

A dimensionless correlation to determine the cumulative leak-off volume into the rock matrix during the dynamic filtration of a fracturing fluid is presented in the last section. The correlation is developed based on dimensional analysis. The model is validated using data obtained from dynamic leak-off experiments. (Abstract shortened by UMI.)

Recovery of permeability in the presence of oil is higher compared with that in the presence of 100% brine saturated cores. The recovery, especially for linear and crosslinked hydroxypropyl guar (HPG), is greater than 100% of the original permeability and is dependent on shut-in time. The fluid loss additive does not appear to affect regain permeability. The production rate has a positive impact on regain permeability.

The first part of this study presents the results of a series of laboratory experiments conducted to investigate the dynamic leak-off behavior of fracturing fluids in the presence of mobile gas or oil saturation. Fracturing fluid leak-off in low permeability gas saturated and high permeability oil saturated reservoir rocks is examined under conditions of varying fracturing fluid composition, formation permeability, oil composition, and fracturing pressure. The effectiveness of fluid loss additives in controlling the leak-off during multiphase flow near the fracture face is also investigated. In addition, a conceptual model to predict the leak-off in the presence of mobile gas or oil saturation at the fracture face has been developed. The model is validated using data obtained from dynamic leak-off experiments.

In the second part of this study, the extent of impairment in formation permeability to oil due to the leak-off of fracturing fluid in oil reservoirs and subsequent recovery during production is evaluated and characterized. The experiments are conducted with a number of commonly used fracturing fluids. Effect of shut-in time, fluid loss additive, fracturing fluid composition, production rates, and oil composition on the regain permeability of oil reservoirs is investigated.
Keywords: Engineering, Petroleum.; Fluid dynamics.; Hydrocarbons Permeability.; Oil wells Hydraulic fracturing.